PENGARUH BUDAYA KERJA, KEMAMPUAN KERJA, TEAM WORK DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA MEDAN - Fakhrulsyah Mega; Dewi Ratna Bulan Siregar; Dana Syah Putra; Heru Pramana; As Ari (JRMB (Jurnal Riset Manajemen & Bisnis), 2021)
Problem of this study what is influence of job culture on performance. What is influence of   work ability on performance. What is influence of   team work on performance. What is influence of job motivation on  performance. What is influence job culture,   work ability, team work and job motivation on   performance. The purpose of this study to determine and analyze the effect of  job culture on   performance. Determine and analyze the effect of  work ability on   performance. Determine and analyze the effect of team work on   performance. Determine and analyze the effect of job motivation on   performance. Determine and analyze the effect of  job culture, work ability, team work and job motivation on   performance.  Sample in the study is 60 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate job culture  has a positive and significant effect on performance. Work ability  has a positive and significant effect on   performance. Team work  has a positive and significant effect on   performance. Job motivation  has a positive and significant effect on performance. Job culture, work ability, team work and job motivation  has a positive and significant effect on   performance.